REDUCING THE PERIOD OF SEXUAL REST FROM 5 TO 3 DAYS IMPROVES SEMEN QUALITY IN THE POINTER BREED OF DOGS - M. A. Raza; S. M. H. Andrabi (Journal of Animal and Plant Sciences, 2022)
The study investigated the changes in fresh semen quality parameters by reducing the period of sexual rest from the usual 5 days to reduced 3 days in the Pointer breed of dogs. Ten healthy male dogs were selected and were randomly divided into two groups i.e. group A and B with sexual rest of 3 and 5 days, respectively. Arousal / collection time, volume and pH were evaluated for all the three fractions of dog semen, whereas, only sperm rich fraction (SRF) was tested for motility, concentration, morphology and live spermatozoa percentage. Semen collection technique and environmental conditions were kept the same for all the dogs. All the three fractions were collected separately but for homogenous analysis, only SRF was focused for all the parameters in the experiment. Results revealed that sperm concentration was altered significantly in group A 410.880 x106 than group B 461.980 x106 (P < 0.05) while slight changes were observed in volume (group A 2.2 and group B 2.5 ml) and motility (81.860 and 80.340% in group A and Group B respectively). However, negligible effects were seen in pH, live and normal sperm cell percentages. The concentration was reduced in dogs ejaculated after 3 days rest but monthly total sperm count was increased around 18%. Live and Normal sperm percentage was also increased with reduced rest. Improvement in sexual behavior at the terminal stage of the experiments was an interesting observation. Collectively these findings indicate that overall quality of semen improves by reducing the rest time between the ejaculates.
Keywords: Pointer dog semen; ejaculate frequency; sexual rest; seminal parameters; dog semen